The Influence Of The Implementation Of Fish Net Games On Sprint Running Learning Ability - Alamsyah, Syamsul Jabbar; Lengkana, Anggi setia; Adang sudrazat (UNIB Press, 2025)
This study aims to determine the effect of the fish net game on the sprint running learning ability of 35 fifth-grade students at SDN Sekarwangi. The method in this study uses a quantitative pre-experimental one-group pretest and posttest method. Based on the results of the normality test, it is known that the overall pretest data is 0.179 and the posttest is 0.050>0.05, which are normally distributed. Then, in the next test using the homogeneity test, it was found that the significance value (Sig) Based on Mean was 0.987 > 0.05, so it can be concluded that the variance of the experimental group data is the same or homogeneous. Then, it was tested using the paired sample T test, and it was found that the Sig. value showed a result of 0.021<0.05, which means that H₁ is accepted and H₀ is rejected. Then, in the regression analysis, an R-Square value of 0.386 was obtained. This indicates that 38.6% of the variability in the dependent variable (post-test) can be explained by the independent variable (pre-test), while the remaining 61.4% is influenced by other factors or contributions from other variables. Conclusion, that the results of sprint running learning can be influenced by the fishnet game.